2008
DOI: 10.1016/s1472-6483(10)60151-4
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to environmental toxins in males seeking infertility treatment: a case-controlled study

Abstract: This case-control study explored the role of environmental toxins in male infertility in patients attending an assisted reproduction clinic in southeastern Spain. Exposures were compared by questionnaire for 30 infertile oligoasthenoteratozoospermic males (cases) and 31 normozoospermic controls residing in the area. Odds ratios and 95% confidence intervals (CI) were used to estimate differences in lifestyle and chemical occupational exposures. More than two-thirds of the cases (23/30), compared with less than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 81 publications
0
36
0
Order By: Relevance
“…It was considered that the person had a previous occupational toxic exposure if he answered that he had been exposed to any of the chemicals that were listed. Detailed information of this study methodology may be found elsewhere (22).…”
Section: Data Collectionmentioning
confidence: 99%
“…It was considered that the person had a previous occupational toxic exposure if he answered that he had been exposed to any of the chemicals that were listed. Detailed information of this study methodology may be found elsewhere (22).…”
Section: Data Collectionmentioning
confidence: 99%
“…Association has been found between welder and reduced sperm count and motility [46,54] . In other case-controlled studies infertile men had been more frequently exposed to organic solvents [52,53,56] , electromagnetic fields and heavy metals than fertile men [46,53,55] . Several solvents affect human semen quality [17,51] , proportionally to the amount and time of exposure [52,53] .…”
Section: Occupational and Environmental Factorsmentioning
confidence: 90%
“…In other case-controlled studies infertile men had been more frequently exposed to organic solvents [52,53,56] , electromagnetic fields and heavy metals than fertile men [46,53,55] . Several solvents affect human semen quality [17,51] , proportionally to the amount and time of exposure [52,53] . Semen quality in workers exposed occupationally to hydrocarbons like toluene, benzene and xylene lead to existence of anomalies in viscosity, liquefaction capacity, sperm count, sperm motility and proportion of sperm with normal morphology compared with unexposed males [57,58] .…”
Section: Occupational and Environmental Factorsmentioning
confidence: 90%
“…The implication of toxins such as glues, volatile organic solvents, silicones, physical agents, chemical dusts and pesticides in infertility has already been established [17]. Radiations and excessive heat to the genitalia have damaging effect on the testicles.…”
Section: Major Causes Of Male Infertilitymentioning
confidence: 99%